Effects and mechanisms of biochar-microbe interactions in soil improvement and pollution remediation: A review - Zhu, Xiaomin; Chen, Baoliang; Zhu, Lizhong; Xing, Baoshan (Environmental pollution (1987), 2017)
Biochars have attracted tremendous attention due to their effects on soil improvement; they enhance carbon storage, soil fertility and quality, and contaminant (organic and heavy metal) immobilization and transformation. These effects could be achieved by modifying soil microbial habitats and (or) directly influencing microbial metabolisms, which together induce changes in microbial activity and microbial community structures. This review links microbial responses, including microbial activity, community structures and soil enzyme activities, with changes in soil properties caused by biochars. In particular, we summarized possible mechanisms that are involved in the effects that biochar-microbe interactions have on soil carbon sequestration and pollution remediation. Special attention has been paid to biochar effects on the formation and protection of soil aggregates, biochar adsorption of contaminants, biochar-mediated transformation of soil contaminants by microorganisms, and biochar-facilitated electron transfer between microbial cells and contaminants and soil organic matter. Certain reactive organic compounds and heavy metals in biochar may induce toxicity to soil microorganisms. Adsorption and hydrolysis of signaling molecules by biochar interrupts microbial interspecific communications, potentially altering soil microbial community structures. Further research is urged to verify the proposed mechanisms involved in biochar-microbiota interactions for soil remediation and improvement. [Display omitted] •Biochar-microbial interactions and mechanisms in soil were reviewed.•Effect mechanisms of biochar on microbial activities were highlighted.•Biochar altered soil carbon sequestration related microbial functions.•Biochar as electron shuttle can enhance contaminant mitigation and remediation.•Potential biochar-microbial interactions on soil improvement were prospected. The interaction mechanisms between biochar and soil microbes and the environmental effects of biochar-microbe interactions on soil carbon sequestration and contaminant mitigation are reviewed.